İslâm hukukunda hakkın düşmesi - Yakar, Fatih (My University, 2010)
Hakkın düşmesi hukukun; olay, eylem ya da işlemlere bağladığı sonuç olarak tanımlanabilir. Bu tanımda hakkın düşmesinin üç tane sebebinin olduğu görülmektedir. Bunlar; hukûkî olay, hukûkî eylem ve hukûkî işlemdir. Hakkın düşmesinin ortaya çıktığı hukûkî durumlar birbirinden farklı özellikler taşır. Bu farklılık, hakkın düşmesinin hukûkî mahiyet ve içeriğini de şekillendirir. Rıza, ferağat, imkânsızlık, cezâî müeyyide, zamanın geçmesi, hakkın düşmesinin mahiyetini izah eden temel kavramlar olarak sıralanabilir. Hakkın düşmesi bazen bireyin rızasına dayalı olarak ortaya çıkarken, kimi zaman imkânsızlık (ölüm gibi) hakkın düşmesinin sebebi olmaktadır. Bazen de hukukun bireye eylemleri nedeniyle ceza vermesi hak kaybını ifade eder. Belirtilmesi gerekir ki, İslâm hukukunda zamanın geçmesi, hakkın özüne ilişkin bir kaybı doğurucu nitelikte değildir.

Forfeiting of the right has been defined as a rusult which has been connected to the case, deed and processing throgh jurisprudence. It can be seet that in this definition there should be three reasons for forfeiting o the right. These are; judicial ase, judicial deed and judicial processing. Judicial cases which have been appeared in forfeiting of the right differs from each other in characteristics. This difference gives shape to the judicial nature and content. Approval, renunciation, impossibitity, penal sanction and passing of the time can be put in order to explain basic concepts in comprehension of the nature of forfeiting of the right. Forfeiting of the right has been occasionally actualized through the approval of the individual and sometimes causes to lose of the right through impossibility (like death). Now and then, penalizing of the jurisprudence for the individual because of his deeds could be stated as forfeiting of the right. Besides, passing of the time colud not be observed as a right-loser state in Islamic Jurisprudence.
Keywords: İslam Hukuku